The development of a microcomputer-based laboratory (MBL) system for gas pressure law experiment and the perception study - Tho, Siew Wei (Tanjong Malim, 2010)
The development of a microcomputer-based laboratory (MBL) system for gas pressure law experiment and the perception study by Tho, Siew Wei